Impervious Surface Thresholds and the Pace to Plant Technique for Planting Urban Red Maple Trees - Adam G. Dale; Steven D. Frank; Elsa Youngsteadt; Barbara Fair; Julieta Sherk; Michael Just (EDIS)
A foundation of integrated pest management (IPM) in urban landscapes is to put the right plant in the right place. This preventive tactic can reduce plant stress, pest infestations, and subsequent pesticide applications. Many urban tree species have more insect and mite pests in urban landscapes than in surrounding natural areas. This is due in part to stress created by impervious surfaces, such as roads and sidewalks that can increase air temperature and reduce soil moisture. For red maples (Acer rubrum), more impervious surface area leads to more stress and worse tree condition. This publication focuses on selecting red maple planting sites that will help reduce tree stress and scale insect pests by maximizing surfaces permeable to water.